Tax Smoothing in a Business Cycle Model with Capital-Skill Complementarity - Konstantinos Angelopoulos; Stylianos Asimakopoulos; Jim Malley (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper undertakes a normative investigation of the quantitative properties of optimal tax smoothing in a business cycle model with state contingent debt, capital-skill complementarity, endogenous skill formation and stochastic shocks to public consumption as well as total factor and capital equipment productivity. Our main finding is that an empirically relevant restriction which does not allow the relative supply of skilled labour to adjust in response to aggregate shocks, significantly changes the cyclical properties of optimal labour taxes. Under a restricted relative skill supply, the government finds it optimal to adjust labour income tax rates so that the average net returns to skilled and unskilled labour hours exhibit the same dynamic behaviour as under flexible skill supply.
Keywords: E13; E32; E62; 330; skill premium; tax smoothing; optimal fiscal policy